Scratch: Programming for All. - RESNICK, MITCHEL; MALONEY, JOHN; MONROY-HERNÁNDEZ, ANDRÉS; RUSK, NATALIE; EASTMOND, EVELYN; BRENNAN, KAREN; MILLNER, AMON; ROSENBAUM, ERIC; SILVER, JAY; SILVERMAN, BRIAN; KAFAI, YASMIN (Communications of the ACM, 2009)
The authors discuss their efforts to make computer programming accessible and the principles that guided them in designing their programming language, Scratch. Scratch, available at http://scratch.mit.edu, is aimed toward children between the ages of eight and 16 to encourage their digital fluency. The philosophy of the authors is that digital fluency involves more than the ability to chat, interact and search, but also the ability to design new media. They suggest that programming encourages computational thinking and problem-solving processes.